Dewabrata's Loyalty - Lany Setyawati (Kanisius, 2009)
After being left by his beloved wife, king sentanu, the king of astinapura wanted to marry again. Princess setyawati was willing to, provided that her descrendant should inherit throne of astinapura kingdom.